2004
DOI: 10.1007/bf03030870
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forecasts of kharif rice in orissa state-four year experience of fasal pilot study

Abstract: Considering the requirement of multiple pre-harvest crop forecasts, the concept of Forecasting Agricultural output using Space, Agrometeorology and Land based observations (FASAL) has been formulated. Development of procedure and demonstration of this technique for four in-season forecasts for kharif rice has been carried out as a pilot study in Orissa State since 1998. As the availability of cloud-free optical remote sensing data during kharif season is very poor for Orissa state, multi-date RADARSAT SCANSAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…It revealed strong relations (i.e., R 2 in the range 0.93 to 0.95 and RMSE in the range 30,519 to 37,451 ha, at 23 district-levels) between modeled and ground-based area estimates. Our results were also similar to other studies: Panigrahy et al (1997) obtained accuracies in the range 85.8 to 91.5% in the early estimation of rice areas in Wet Bengal, India; (ii) Patel et al (2004) found approximately 95% accuracy in forecasting Kharif rice acreage in Orissa, India; (iii) Chen et al (2011) In addition, we also compared the boro rice area estimated using only two images acquired during the initial/transplantation and peak greenness stages in the scope of this paper with those extracted in an earlier study (Mosleh & Hassan, 2014). In that study, we employed ten 16-day composite of NDVI images acquired over the entire growing season and estimated the boro rice area after the harvesting of the crop.…”
Section: Delineation Of Areas Under Rice Cultivationsupporting
confidence: 92%
“…It revealed strong relations (i.e., R 2 in the range 0.93 to 0.95 and RMSE in the range 30,519 to 37,451 ha, at 23 district-levels) between modeled and ground-based area estimates. Our results were also similar to other studies: Panigrahy et al (1997) obtained accuracies in the range 85.8 to 91.5% in the early estimation of rice areas in Wet Bengal, India; (ii) Patel et al (2004) found approximately 95% accuracy in forecasting Kharif rice acreage in Orissa, India; (iii) Chen et al (2011) In addition, we also compared the boro rice area estimated using only two images acquired during the initial/transplantation and peak greenness stages in the scope of this paper with those extracted in an earlier study (Mosleh & Hassan, 2014). In that study, we employed ten 16-day composite of NDVI images acquired over the entire growing season and estimated the boro rice area after the harvesting of the crop.…”
Section: Delineation Of Areas Under Rice Cultivationsupporting
confidence: 92%
“…Kharif rice which happens to be dominant crop of the state has been chosen for demonstrating multiple forecasts at district level. Four in-season forecasts were made during kharif seasons (Patel et al, 2004); the first forecast of rice acreage at the beginning of kharif crop season using meteorological models, second forecast of district level acreage at mid growth season using two-date RADARSAT SCANSAR data and yield using meteorological models, third forecast at late growth season of district level acreage using three-date RADARSAT SCANSAR data and yield using meteorological models and revised forecast incorporating field observations at maturity. Summary results of FASAL Pilot Implementation for Kharif rice forecasts for 2006-07 are given in Table 2.…”
Section: Fasal Implementation -Orissamentioning
confidence: 99%
“…Advanced techniques of satellite remote sensing and Geographic Information System (GIS) are now available to derive spatial pattern of crop area, cropping pattern change, crop calendar and crop rotation etc. (Navalgund et al, 1991;Parihar and Dadhwal, 2002;Rajak et al, 2002;Rajak et al, 2008;Panigrahy et al, 2005;Panigrahy & Sharma, 1997;Patel et al, 2004). High temporal resolution data is essential to analyze the crop calendar.…”
Section: Introductionmentioning
confidence: 99%